Application effect of NRS2002 scale in perioperative nutritional intervention of patients undergoing radical cystectomy - Cai, Yibo; Lou, Jinhan (Progress in Nutrition, 2022)
Objective: This study aimed to explore the effect of nutritional intervention based on the NRS2002 scale in perioperative nutritional intervention in radical cystectomy for bladder cancer. Methods: A total of 65 patients with bladder cancer who were treated in our hospital from January 2019 to January 2020 and who met the inclusion and exclusion criteria were enrolled as the subjects. These patients were randomly divided into a control group and an experimental group. The patients in the control group received routine perioperative nutritional intervention, and the patients in the experimental group were given nutrition intervention based on NRS2002. The quality of life, nursing satisfaction rate, nutritional indexes (serum albumin, transferrin, and prealbumin), and body mass index (BMI) before and after intervention were compared between the two groups. Results: The differences in nursing satisfaction rate, sleep, appetite, interpersonal communication, daily activities, and mental state scores between the two groups were statistically significant (P < 0.05). The levels of prealbumin, transferrin, albumin, and BMI in the experimental group were higher than those in the control group, and the differences were statistically significant (P < 0.05). Conclusion: The perioperative nutritional intervention based on NRS2002 for patients undergoing total cystectomy can not only significantly improve the perioperative nutritional level and BMI but also improve the quality of life and nursing satisfaction. This is worthy of clinical popularization.